PERSEPSI MASYARAKAT TERHADAP PEREMPUAN BEKERJA DI PERKEBUNAN KELAPA SAWIT DESA SALIKI, KECAMATAN MUARA BADAK, KABUPATEN KUTAI KARTANEGARA - Norhadi Norhadi; Yayuk Yulianti; Reza Safitri (Universitas Sebelas Maret, 2019)
The role of women is no longer associated with their nature as housewives but has developed to work in the public sector, this research method is qualitative descriptive research. The focus of the research is the people in Saliki Village. The data used are primary data sources and secondary data. Data collection using field research consists of observation, interviews, and documentation. Qualitative analysis techniques of Miles Huberman and Saldana. The perception of the people in Saliki Village provides positive things and supports women working as laborers on oil palm plantations, with the aim of helping the family economy, time to gather and interact with limited communities and social activities are not always time, but still maintained relationships and good friends with the community in Saliki Village. The role of women in the public sector is well run and in the domestic sector remains responsible as a housewife.